Some properties of probabilistic one-sided sticker systems - Selvarajoo, Mathuri; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (2013)
A sticker system, introduced by Kari in 1998, is an abstract computational model that uses the Watson-Crick complementary feature of DNA molecules: starting from the incomplete double stranded sequences and iteratively using sticking operations until a complete double stranded sequence is obtained. It is known that sticker systems with finite sets of axioms and sticker rules generate only regular languages. Hence, different types of restrictions have been considered to increase the computational power of sticker systems. Recently, a variant of restricted sticker systems, called probabilistic sticker systems, has been introduced. In these models, the probabilities are initially associated with the axioms, and the probability of a generated string is computed by multiplying the probabilities of all occurrences of the initial strings in the computation of the string. In this paper, some properties of probabilistic one-sided sticker systems are investigated. We prove that the probability restriction can increase the computational power of one-sided sticker systems.